Korean quality – past, present, and future. (3rd July 2016) - Shin, Wan Seon; Park, Heejun
Abstract : The article discusses the key activities in the process of enhancing quality to attain excellence in Korea by investigating the key issues addressed by both government and scholars over the past 60 years. The key quality initiatives were classified by decade and presented customer needs, government policies, and objectives at each of the six decades. A thorough counting process using the research articles published in Korea was also conducted to delineate the main research themes. The current strengths and weaknesses of Korean quality were summarised according to MBQ (Motivation-based Quality), SBQ (System-based Quality), and KBQ (Knowledge-based Quality). Finally, a set of strategic issues were identified and converted into five long-term tasks required to create a new slope for the future of Korean quality. We regard this study as unique in that it summarises Korea's long-term quality initiatives of the past 60 years and proposes new strategic issues for the future of Korean quality. The results of this study are expected to provide policy-makers and scholars with a new understanding of Korea's quality movement from the Past to the Present and the Future .